Theoretical investigation of bonding type effect in ferrocene dimers on electric and thermoelctric proteprties - Jasim, Rasha Talal; Noori, Mohammed Deia (Edelweiss Applied Science and Technology, 2024)
Thermoelectric materials possess the capacity to significantly impact worldwide energy usage by virtue of their capability to transform heat into electrical energy. However, the majority of these materials exhibit low efficiency. Currently, there are ongoing studies exploring the thermoelectric properties of molecular junctions and low-dimensional structures. These investigations aim to identify and evaluate new nanostructure systems that can overcome the existing limits. In this study, we have conducted a theoretical comparison of the electrical and thermoelectric properties of four distinct topologies of ferrocene dimers. The findings of our study indicate that the connectivity and bonding type between ferrocene dimer units play a crucial role in controlling the quantum interference (QI) and enhancing the thermoelectric properties of these molecular junctions. These structures are highly promising for use as thermoelectric enhancers and are well-suited for many thermoelectric applications.